Kajian Teologis tentang Keselamatan dan Pengampunan serta Implikasinya terhadap Orang Percaya - Rika Rika; Nova Nova; Flora Ferlin Lipungan (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
This study explores the concepts of salvation and forgiveness in Christian theology, with a focus on contemporary implications and challenges in the digital age. Through theological analysis, the concept of salvation is understood as God's gift that changes character, while forgiveness becomes a call to practice love in social interactions. Contemporary challenges, including relevance in the digital age and the impact of controversial content, are driving the adaptation of these values. Believers are expected to be agents of change in building an inclusive and tolerant society. Implications for everyday life include character transformation and the role of believers in overcoming digital conflicts. In conclusion, the concepts of salvation and forgiveness are not only a theological basis, but also a source of inspiration for forming positive behavior in the dynamics of the contemporary world.